PSVIII-19 Evaluation of Cooling Pads on Late Lactating Sows. (30th November 2020) - Shirley, Larissa; Burgett, Morgan; Field, Tyler; Schinckel, Allan P; Stewart, Kara R; Garcia, Ricardo M; Johnson, Jay S; Stwalley, Robert
Abstract: An electronically controlled cooling pad has been developed to remove excess heat from sows using water cooled by flowing through underground pipes. This study was designed to evaluate different water flush rates on physiological measures of heat stress on day 16 to 21 of lactation. Twelve sows were randomly assigned to 3 treatments (control (CN), flush 2.0 L over 30 sec every 2.5 minutes (F2.5), or flush every 5 minutes (F5)) in a Latin square design. Feed intake (FI) was recorded daily at 0700 h. Temperatures were gradually increased from 22°C at 0800 h to 32°C by 0930 h. Then 32°C was maintained until 1500 h, when cooling of the room began. After 1800 h, the cooling pads were flushed every 9 minutes. Rectal temperature (RTemp), skin temperature (STemp), and respiration rates (RR) were measured at 0700, 0730, 0900, 1200, 1500, and 1800 h daily, with thermal imaging (IR) being taken at 1200 and 1500 h. The effects of flush rate (amount of water flushed) on STemp were linear (P=0.023), with means of 35.9, 35.0, and 35.9°C for the CN, F2.5, and F5.0 treatments. Pad flush rate effects of RTemp were linear (P< 0.001) and were greater in CN sows compared to F2.5 and F5 (39.3°, 38.8°, and 38.9°C), P< 0.0001). RR was affected by treatment (60 vs 42 and 50 breaths/min, P< 0.005 for CN, F2.5, and F5.0 treatments). Treatment by time interactions were significant for RR (P=0.0003) and RTemp (P=< 0.0001), with the greatest differences at 1200 and 1500 times (RR = 89, 48, & 65; and RTemp 39.9, 39.0, & 39.2°C for CN, F2.5, and F5.0 treatments). Skin temps measured by thermal imaging were not different among treatments (P=0.38) nor DFI (P=0.41). Cooling pad use with a flush rate of 2.0 L/2.5 min reduced body temperature to euthermia without increasing RR most effectively. This has implications toward reducing energy expenditure for thermoregulatory processes, which can increase nutrient availability for lactation during HS.